2014
DOI: 10.5604/12321966.1120594
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dioxin intoxication on the human system and possibilities of limiting its negative effects on the environment and living organisms

Abstract: According to recent studies, dioxins are present in different concentrations in the environment and cause specific and long-time effects. These effects could be limited by the use of tocopherol and acetylsalicylic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 70 publications
0
17
0
1
Order By: Relevance
“…Consequently, inflammatory cytokines such as interleukin-1 (IL-1) and tumor necrosis factor (TNF) are released; therefore, fibroblast activity is inhibited and osteoclasts are activated. 3,6,31 During our own research, the inhibition of a negative impact of TCDD on the dental organ in offspring from the TCDD+E group have correlated with an increased AhR expression after administration of E, especially in the layer of odontoblastic and amelogenic cells compared to the offspring of mothers that were exposed to the dioxin only. 6,30 In rat newborns whose mothers were exposed to TCDD, a positive reaction to AhR was present mainly in epithelial cells but it was rare and of low intensity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consequently, inflammatory cytokines such as interleukin-1 (IL-1) and tumor necrosis factor (TNF) are released; therefore, fibroblast activity is inhibited and osteoclasts are activated. 3,6,31 During our own research, the inhibition of a negative impact of TCDD on the dental organ in offspring from the TCDD+E group have correlated with an increased AhR expression after administration of E, especially in the layer of odontoblastic and amelogenic cells compared to the offspring of mothers that were exposed to the dioxin only. 6,30 In rat newborns whose mothers were exposed to TCDD, a positive reaction to AhR was present mainly in epithelial cells but it was rare and of low intensity.…”
Section: Discussionmentioning
confidence: 89%
“…1,2 Our study and those of other authors showed that TCDD induces inflammatory processes and activates the processes of enzymatic digestion of connective tissue elements. 3,4 On the other hand, dioxins inhibit alkaline phosphatase in osteoblasts, thus disturbing the mineralization process. 5,6 Moreover, TCDD inhibits collagen I synthesis by altering gene expression and induces oxidative stress, leading to the activation of interleukins, which further activate osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important that substances are found that can protect against the negative effects of dioxins. The proinflammatory effects of TCDD can be eliminated using antioxidant compounds, such as α-tocopherol (vitamin E), or nonsteroidal anti-inflammatory drugs such as acetylsalicylic acid (ASA) (Całkosiński et al 2014). It has previously been found that these pharmaceuticals are AhR antagonists that can inhibit the inflammatory reactions induced by dioxins (Kloser et al 2011; MacDonald et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocarbons (the bulk of the tyre and firewood) and oxygen (from the air) are readily available when tyre is incinerated. Most thermal process leads to the formation of dioxins, because they are characterized by the presence of organic matter, chlorine, high temperature (200-900°C) and low concentration of oxygen [7]. One important source of chlorine in tyres is its content of halogenated butyl rubber liners.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the presence of metals in tyres serve as catalyst for the synthesis of dioxin, providing a surface on which dioxins can readily form during and after the combustion process. Dioxins are highly toxic and cause serious health problems such as infertility, learning disabilities, endometriosis, sexual reproductive disorders, birth defects, damage to the immune system and cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%